LLZO-based composite solid electrolyte prepared by solvent-free method as well as preparation method and application of LLZO-based composite solid electrolyte
The LLZO-based composite solid electrolyte is prepared by the solvent-free method, and the dual role of ion gel filling of electrolyte particles and PTFE binder is solved, and the problem of low solvent use and lithium ion transmission efficiency in traditional methods is achieved, and an electrolyte membrane with high ion conductivity and good interface stability is achieved.
Patent Information
- Application Number
- CN202510078992.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-17
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2045-01-17
AI Technical Summary
In the prior art, when preparing LLZO-based composite solid electrolyte membranes, toxic and expensive organic solvents are needed, and the casting process consumes energy and is not conducive to zero-emission manufacturing. At the same time, the high hardness of the garnet-type electrolyte results in low lithium ion transmission efficiency of the electrolyte membrane.
The LLZO-based composite solid electrolyte was prepared by solvent-free method. The ionic gel was formed by mixing PDADMAFSI, LiFSI and PyR13FSI, and ball milling was mixed with lithium lanthanum zirconium oxy-based solid electrolyte powder and PTFE. After adding the ionic gel, the ball milling was continued to form an electrolyte with good interfacial conduction and flexibility characteristics.
It improves the interface conduction between electrolyte particles, improves ionic conductivity, hinders the side reaction between PTFE binder and metal lithium, extends the cycle life and structural stability of the battery, and realizes an environmentally friendly solvent-free preparation process.
Smart Images

Figure CN119852503A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of solid electrolytes, and in particular relates to a solvent-free LLZO-based composite solid electrolyte and a preparation method and application thereof. Background Art
[0002] The statements herein merely provide background information related to the present invention and do not necessarily constitute prior art.
[0003] Lithium-ion batteries have become an important source of power for electric vehicles and grid-scale energy storage. However, traditional lithium-ion batteries use flammable liquid electrolytes and flammable organic polymer separators, which pose safety risks during use, and their energy density is gradually approaching the theoretical limit. In this context, the development of all-solid-state batteries, replacing flammable liquid electrolytes and organic separators with inorganic solid electrolytes, is considered a strategic approach to spontaneously improve energy density and safety. Among them, garnet-type solid electrolytes LLZO have attracted great research interest due to their many advantages, including low cost, high lithium ion conductivity, high Young's modulus, high electrochemical stability, wide electrochemical window, and good compatibility with lithium metal. However, due to the high hardness of LLZO-based solid electrolytes, large-scale production of solid electrolyte membranes still faces great challenges.
[0004] Polymer solid electrolytes (SPEs) have been widely studied due to their excellent flexibility, film-forming ability, and compatibility with positive and negative electrodes. However, polymer solid electrolytes have low lithium ion conductivity, low Young's modulus values, and poor thermal stability, which limit their use in large-scale applications. To address this issue, garnet solid electrolytes and polymer solid electrolytes have been used to fabricate composite electrolyte membranes. The composite electrolyte membranes have the excellent flexibility and processability of polymer solid electrolytes, as well as the excellent mechanical strength, thermal stability, and excellent lithium ion conductivity of garnet electrolytes. However, the main method for preparing LLZO-SPE-based composite electrolyte membranes is the casting method. However, casting requires toxic and expensive organic solvents, which reduces the practical applicability of using this method to prepare electrolyte membranes. In addition, solvent evaporation requires an energy-consuming heating process, which is not conducive to achieving zero-emission manufacturing.
[0005] In recent years, the process of interweaving inorganic solid electrolytes into independent solid electrolyte membranes using polytetrafluoroethylene (PTFE) fiberization technology has attracted much attention. The preparation process does not require any solvent. For example, there has been a study that premixed and ground garnet-type electrolyte powder and commercial PTFE powder, and then rolled at room temperature to generate a garnet solid electrolyte membrane. However, due to the high hardness of the garnet-type electrolyte, there are obvious gaps between the self-supporting electrolyte membrane particles obtained using this scheme, which seriously hinders the transmission of lithium ions therein and reduces the overall ionic conductivity of the electrolyte; in addition, there are side reactions between PTFE and metallic lithium, which increases the interfacial resistance and reduces the battery efficiency. Summary of the invention
[0006] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a solvent-free LLZO-based composite solid electrolyte and its preparation method and application. The solvent-free LLZO-based composite solid electrolyte provided by the present invention not only enhances the interface conduction between electrolyte particles and improves the ionic conductivity, but also hinders the side reaction between the PTFE binder and the metallic lithium, avoids the formation of a deteriorated interface, and improves the cycle life of the full battery and the structural stability of the battery.
[0007] In order to achieve the above object, the present invention is implemented through the following technical solutions:
[0008] In a first aspect, the present invention provides a method for preparing a LLZO-based composite solid electrolyte by a solvent-free method, comprising the following steps:
[0009] Poly(diallyldimethylammonium)bis(fluorosulfonyl)imide (PDADMAFSI), lithium bis(fluorosulfonyl)imide (LiFSI) and N-butyl-N-methylpyrrolidine bis(trifluoromethylsulfonyl)imide (PyR 13 FSI) are mixed in a molar ratio of 1:1-1.5:2-4, and stirred at 70-90° C. to obtain a solid ion gel;
[0010] The lithium lanthanum zirconium-based solid electrolyte powder and polytetrafluoroethylene (PTFE) are mixed and ball-milled for a set time, and the PTFE accounts for 2 to 5 wt.% of the total mass of the lithium lanthanum zirconium-based solid electrolyte and the PTFE; then the ion gel is added thereto in proportion, and the ball milling is continued until the mixture is uniform, and the mass ratio of the ion gel to the PTFE is 5 to 10:1, so as to obtain a solid electrolyte.
[0011] In some embodiments, PDADMAFSI, lithium bis(fluorosulfonyl)imide (LiFSI), and PyR 13 The FSI mixing and stirring time is 12 to 18 hours.
[0012] In some embodiments, the lithium lanthanum zirconium oxide solid electrolyte powder and PTFE are mixed and ball-milled for 0.5-2 hours, and the rotation speed of the ball mill is 200-300 rpm.
[0013] Preferably, after the ion gel is added, the ball milling time is continued for 1-3 hours, and the ball milling speed is 500-800 rpm.
[0014] In some embodiments, the lithium lanthanum zirconium-based solid electrolyte is selected from one of LLZO, LLZTO, LLZNO, or LALZO.
[0015] In some embodiments, the step of hot rolling the prepared solid electrolyte and then thinning it to a set thickness by rolling to obtain an electrolyte membrane is also included.
[0016] Preferably, the hot rolling temperature is 80-90°C.
[0017] Preferably, a double-roller machine is used to roll-thin the electrolyte membrane, and the rolling-thinning temperature is 80-90°C.
[0018] Preferably, the thickness of the obtained electrolyte membrane is 80-100 μm.
[0019] In a second aspect, the present invention provides a solvent-free LLZO-based composite solid electrolyte prepared by the preparation method.
[0020] In a third aspect, the present invention provides the use of the solvent-free LLZO-based composite solid electrolyte in the preparation of a solid-state lithium-ion battery.
[0021] In some embodiments, the positive electrode material of the solid-state lithium-ion battery is lithium iron phosphate, lithium cobalt oxide, lithium manganese oxide or a ternary lithium positive electrode material.
[0022] The beneficial effects achieved by one or more embodiments of the present invention are as follows:
[0023] (1) The particles of the solvent-free LLZO-based composite solid electrolyte provided by the present invention are filled with ion gel with certain viscoelasticity, so the internal contact of the electrolyte is tight without gaps, which is beneficial to inhibiting the growth of lithium dendrites.
[0024] (2) The solvent-free LLZO-based composite solid electrolyte provided by the present invention forms a continuous ion transmission channel inside, thereby having high ion conductivity, which is conducive to the rapid transmission of lithium ions inside the electrolyte and at the interface;
[0025] (3) The solvent-free LLZO-based composite solid electrolyte provided by the present invention has good flexibility and processability under the dual effects of PTFE binder and ion gel;
[0026] (4) The solvent-free LLZO-based composite solid electrolyte provided by the present invention hinders the side reaction between the PTFE binder and metallic lithium and has good interface stability;
[0027] (5) The solvent-free LLZO-based composite solid electrolyte LLZO-IPL provided by the present invention can stably cycle for more than 500 cycles when applied to solid-state lithium metal batteries.
[0028] (6) The preparation method of the present invention is simple and can be mass-produced; the preparation process is environmentally friendly and does not require any toxic organic solvents. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] The accompanying drawings in the specification, which constitute a part of the present invention, are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute improper limitations on the present invention.
[0030] Figure 1 This is a planar scanning electron microscope image of the LLZTO-IPL composite solid electrolyte prepared by a solvent-free method in an embodiment of the present invention.
[0031] Figure 2 This is a planar scanning electron microscope image of the LLZTO solid electrolyte membrane prepared by the solvent-free method in an embodiment of the present invention.
[0032] Figure 3 The impedance spectra of the LLZTO-IPL based composite solid electrolyte prepared by the solvent-free method at different temperatures in an embodiment of the present invention.
[0033] Figure 4 The impedance spectra of the LLZTO solid electrolyte prepared by the solvent-free method at different temperatures in an embodiment of the present invention.
[0034] Figure 5 This is the constant current voltage cycle curve of a symmetrical battery assembled with the LLZTO-IPL composite solid electrolyte based on LLZTO prepared by a solvent-free method in an embodiment of the present invention.
[0035] Figure 6 This is the constant current voltage cycle curve of a symmetrical battery assembled with the LLZTO solid electrolyte prepared by the solvent-free method in an embodiment of the present invention.
[0036] Figure 7 This is the full-cell electrochemical performance cycle curve of the LLZTO-IPL composite solid electrolyte prepared by the solvent-free method in the embodiment of the present invention.
[0037] Figure 8 Full-cell electrochemical performance cycle curve of LLZTO electrolyte prepared by solvent-free method.
[0038] Fig. 9 This is a plane scanning electron microscope image of the solid electrolyte membrane of Comparative Example 2 of the present invention.
[0039] Fig.10 This is a scanning electron microscope image of a cross section of the solid electrolyte membrane of Example 1 of the present invention.
[0040] Fig.11 This is a bending optical photograph of Example 1 of the present invention. DETAILED DESCRIPTION
[0041] It should be noted that the following detailed descriptions are illustrative and intended to provide further explanation of the present invention. Unless otherwise specified, all technical and scientific terms used in the present invention have the same meanings as those commonly understood by those skilled in the art to which the present invention belongs.
[0042] The present invention will be further described in detail below in conjunction with specific embodiments. It should be noted that the specific embodiments are intended to explain the present invention rather than to limit it.
[0043] Example 1
[0044] The preparation method of the solvent-free LLZTO composite solid electrolyte comprises the following steps:
[0045] Step 1: Weigh 0.102 g of PDADMAFSI, 0.093 g of LiFSI and 0.6 g of PyR 13 FSI was heated at 80 °C with magnetic stirring for 14 h to obtain yellow ion gel IPL.
[0046] Step 2: Weigh 3 g of LLZO nanopowder and 0.12 g of PTFE powder and place them in a ball mill, then mechanically mix and ball mill at a speed of 200 rpm for 1 hour, then scrape the powder on the inner wall of the ball mill, add the ion gel IPL obtained in step 1, and then ball mill again at a speed of 500 rpm for 1 hour.
[0047] Step 3: The flocculent block obtained after ball milling was taken out and placed on a heating plate in a glove box, and manually hot-rolled into an electrolyte membrane LLZTO-IPL using a stainless steel cylindrical rod at 85°C. In order to further reduce the thickness of the electrolyte and improve the contact between the electrolyte particles, the LLZTO-IPL was rolled to 80 μm using a double-roller at 85°C. Finally, it was cut into discs with a diameter of 16 mm and placed in the glove box for use.
[0048] Comparative Example 1
[0049] Compared with Example 1, the difference is that this comparative example does not include ion gel IPL, and the specific preparation process is as follows:
[0050] Step 1: Weigh 3 g of LLZO nanopowder and 0.12 g of PTFE powder and place them in a ball mill, then mechanically mix and ball mill at a rotation speed of 200 rpm for 1 hour.
[0051] Step 2: Take out the flocculent block obtained in step 1 and place it on a heating plate in the glove box, and manually hot-roll it into an electrolyte membrane LLZTO using a stainless steel cylindrical rod at 85°C. Then, LLZTO is repeatedly rolled to 80 μm using a double-roller at 85°C. Finally, it is cut into discs with a diameter of 16 mm and placed in the glove box for standby use.
[0052] Comparative Example 2
[0053] Compared with Example 1, the difference is that in step 2 of this comparative example, 0.1 g of ion gel IPL is added, and the rest is the same as Example 1.
[0054] Test example
[0055] Assembly of symmetrical batteries: Place two lithium sheets with a diameter of 12 mm symmetrically on both sides of a solid electrolyte with a diameter of 16 mm, and place them in a 2032-type battery shell in the order of gasket, lithium sheet, solid electrolyte, lithium sheet, gasket, and shrapnel, and finally seal it using a battery packaging machine.
[0056] Assembly of button batteries: A lithium sheet with a diameter of 12 mm is used as the negative electrode, a solid electrolyte with a diameter of 16 mm is used as the electrolyte, and a lithium iron phosphate electrode with a diameter of 12 mm is used as the positive electrode. The 1 mm thick gasket, negative electrode, electrolyte, positive electrode, gasket, and spring are placed in order from bottom to top, and then packaged in a 2023 type battery shell through a battery packaging machine.
[0057] Figure 1 This is a planar scanning electron microscope image of the solvent-free LLZTO-based composite solid electrolyte LLZTO-IPL. From the image, it can be seen that the electrolyte surface is flat and smooth, and there are no obvious gaps between the electrolyte particles, proving that lithium ions can form a continuous transmission channel inside the electrolyte.
[0058] Figure 2 This is a planar scanning electron micrograph of the LLZTO electrolyte membrane obtained by dry process without ion gel composite. It can be seen from the figure that under the action of PTFE fibrillation, the electrolyte particles can form an independent self-supporting film, but the contact between the particles is poor, and there are a large number of obvious gaps.
[0059] Figure 3 The impedance spectra of LLZTO-IPL electrolyte at different temperatures show that the ionic conductivity of LLZTO-IPL electrolyte at room temperature is 2.5x10 -4 S / cm, can be increased to 1.1x10 at 70℃ -3S / cm.
[0060] Figure 4 The impedance spectra of the LLZTO electrolyte membrane prepared by dry process at different temperatures show that the ionic conductivity of the LLZTO membrane electrolyte at room temperature is 8.48x10 -5 S / cm, the ionic conductivity of LLZTO-IPL electrolyte membrane is three times that of LLZTO-IPL electrolyte membrane.
[0061] Figure 5 The electrochemical stability of the LLZTO-IPL electrolyte membrane is shown in the figure. -2 At a current density of 1.34 W, the symmetrical battery assembled with LLZTO-IPL electrolyte membrane maintained a stable overpotential and a cycle life of up to 800 hours.
[0062] Figure 6 This is the symmetrical battery cycle voltage curve of the LLZTO electrolyte membrane. It can be seen from the figure that with the extension of the cycle time, the polarization voltage gradually increases. This is because the side reaction between PTFE and metallic lithium causes the contact to deteriorate and forms by-products with large impedance. With the continuous accumulation of by-products, the battery eventually fails after about 300 hours of cycle.
[0063] Figure 7 It can be seen that the button battery with LLZTO-IPL electrolyte membrane prepared by solvent-free method can stably cycle 1000 times at a current density of 0.5C (85mA / g) and then charge and discharge at a constant rate.
[0064] Figure 8 This is a full battery using LLZTO electrolyte membrane cycled at the same current density. It can be seen that the discharge capacity decays rapidly after 100 cycles, and the capacity drops to 75 mAh / g after 300 cycles.
[0065] Fig. 9 The planar scanning electron microscope image of the electrolyte membrane of Comparative Example 2 is shown. It can be seen from the figure that when the amount of ion gel added is 5wt.% of the mass of LLZTO and PTFE, some gaps will still appear between the electrolyte particles, hindering the continuous transmission of lithium ions.
[0066] Fig.10 This is a cross-sectional scanning electron microscope image of the LLZTO-IPL electrolyte membrane prepared by the solvent-free method. From the image, it can be seen that the thickness of the electrolyte membrane is about 80 microns after manual rolling and rolling on a double-roller machine, and the electrolyte particles are densely distributed, which is conducive to resisting lithium dendrite penetration.
[0067] Fig.11 This is a bending optical photograph of Example 1. It can be seen from the figure that the electrolyte membrane has good flexibility.
[0068] Example 2
[0069] The preparation method of the solvent-free LLZTO composite solid electrolyte comprises the following steps:
[0070] Step 1: Weigh 0.06 g of PDADMAFSI, 0.07 g of LiFSI and 0.4 g of PyR 13 FSI was heated at 75 °C with magnetic stirring for 18 h to obtain yellow ion gel IPL.
[0071] Step 2: Weigh 2 g of LLZO nanopowder and 0.08 g of PTFE powder and place them in a ball mill, then mechanically mix and ball mill at a speed of 220 rpm for 1.5 hours. Then, after scraping off the powder on the inner wall of the ball mill, add the ion gel IPL obtained in step 1, and then ball mill again at a speed of 600 rpm for 1 hour.
[0072] Step 3: The flocculent block obtained after ball milling was taken out and placed on a heating plate in a glove box, and manually hot-rolled into an electrolyte membrane LLZTO-IPL using a stainless steel cylindrical rod at 80°C. In order to further reduce the thickness of the electrolyte and improve the contact between the electrolyte particles, the LLZTO-IPL was rolled to 85μm using a double-roller at 80°C. Finally, it was cut into discs with a diameter of 13mm and placed in the glove box for use.
[0073] Example 3
[0074] The preparation method of the solvent-free LLZTO composite solid electrolyte comprises the following steps:
[0075] Step 1: Weigh 0.25 g of PDADMAFSI, 0.2 g of LiFSI and 1.5 g of PyR 13 FSI was heated at 85 °C with magnetic stirring for 12 h to obtain yellow ion gel IPL.
[0076] Step 2: Weigh 5 g of LLZO nanopowder and 0.15 g of PTFE powder and place them in a ball mill, then mechanically mix and ball mill at a speed of 300 rpm for 3 hours, then scrape the powder on the inner wall of the ball mill, add the ion gel IPL obtained in step 1, and then ball mill again at a speed of 800 rpm for 1 hour.
[0077] Step 3: The flocculent block obtained after ball milling was taken out and placed on a heating plate in a glove box, and manually hot-rolled into an electrolyte membrane LLZTO-IPL using a stainless steel cylindrical rod at 90°C. In order to further reduce the thickness of the electrolyte and improve the contact between the electrolyte particles, LLZTO-IPL was rolled to 100 μm using a double-roller at 90°C. Finally, it was cut into discs with a diameter of 14 mm and placed in the glove box for use.
[0078] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing a solvent-free LLZO-based composite solid electrolyte, characterized in that: The steps include: The poly(diallyldimethylammonium)bis(fluorosulfonyl)imide, lithium bis(fluorosulfonyl)imide and N-butyl-N-methylpyrrolidine bis(trifluoromethylsulfonyl)imide are mixed in a molar ratio of 1:1 to 1.5:2 to 4, and stirred at 70 to 90° C. to obtain a solid ion gel; The lithium lanthanum zirconium-based solid electrolyte powder and polytetrafluoroethylene are mixed and ball-milled for a set time, and the PTFE accounts for 2 to 5 wt.% of the total mass of the lithium lanthanum zirconium-based solid electrolyte and the PTFE; then the ion gel is added thereto in proportion, and the ball milling is continued until the mixture is uniform, and the mass ratio of the ion gel to the PTFE is 5 to 10:1, so as to obtain a solid electrolyte.
2. The method for preparing a solvent-free LLZO-based composite solid electrolyte according to claim 1, characterized in that: PDADMAFSI, lithium bis(fluorosulfonyl)imide and PyR 13 The FSI mixing and stirring time is 12 to 18 hours.
3. The method for preparing a solvent-free LLZO-based composite solid electrolyte according to claim 1, characterized in that: The time of mixing the lithium lanthanum zirconium oxide solid electrolyte powder and PTFE by ball milling is 0.5-2h, and the speed of ball milling is 200-300rpm; Preferably, after the ion gel is added, the ball milling time is continued for 1-3 hours, and the ball milling speed is 500-800 rpm.
4. The method for preparing a solvent-free LLZO-based composite solid electrolyte according to claim 1, characterized in that: The lithium lanthanum zirconium-based solid electrolyte is selected from one of LLZO, LLZTO, LLZNO or LALZO.
5. The method for preparing a solvent-free LLZO-based composite solid electrolyte according to claim 1, characterized in that: The method also includes hot rolling the prepared solid electrolyte and then rolling it to reduce the thickness to a set thickness to obtain an electrolyte membrane; Preferably, the hot rolling temperature is 80-90°C.
6. The method for preparing a solvent-free LLZO-based composite solid electrolyte according to claim 1, characterized in that: The electrolyte membrane is rolled and thinned by a double-roller machine, and the rolling and thinning temperature is 80-90°C.
7. The method for preparing a solvent-free LLZO-based composite solid electrolyte according to claim 1, characterized in that: The thickness of the obtained electrolyte membrane was 80-100 μm.
8. A solvent-free LLZO-based composite solid electrolyte, characterized in that: Prepared by the preparation method described in any one of claims 1 to 7.
9. Use of the solvent-free LLZO-based composite solid electrolyte according to claim 8 in the preparation of solid-state lithium-ion batteries.
10. The use according to claim 9, characterized in that: The positive electrode material of the solid-state lithium-ion battery is lithium iron phosphate, lithium cobalt oxide, lithium manganese oxide or a ternary lithium positive electrode material.
Citation Information
Patent Citations
Preparation method of flexible self-supporting electrochromic film
CN110095913A
Amino-containing MOF-based composite gel solid electrolyte with high specific surface area, preparation method and application thereof
CN112670565A
Polyion liquid / active ceramic composite electrolyte and preparation method thereof
CN113178618A
Gel composite positive electrode for solid-state battery and preparation method of gel composite positive electrode
CN113839005A
Liquid composition based on ionic liquid for protecting lithium metal components, related coating and polymerization methods and
CN114730857A